Helyzetmérlegelés és taktika a magyar háborús diplomáciában, 1942-1944 - Joó, András (Közép-Európai Közlemények, 2016)
In 1942 Miklós Kállay accepted Premiership after Regent Horthy had managed to convince him following a series of discussions. They shared the same views concerning the possible outcome of the war, although Kállay seemed more pessimistic at the beginning. Both had the strong belief that the Anglo-American alliance would emerge as the strongest centre of power at the war’s end, thus in a position to determine the fate of Hungary, and the traditional balance of power politics of the British would not be altered significantly. Kállay lacked stable domestic support for his policies, as pro-German political forces remained strong. Hungarian foreign policy decision-makers relied mainly on their experience of the First World War, which ultimately proved to be little help when critical moments were already near. Few of them reckoned with the desperate resistance of Germany until the bitter end. The military balance had changed radically by the end of January 1943, which lead to the final consolidation of the antagonistic cooperation of the Soviets and the West. For Hungary it was very difficult to accept the serious consequences and face the necessary, but least of all desired conclusions. More than only in theory, Kállay and the Hungarian Foreign Ministry officials still saw some avenues open to defect from the German camp successfully, preserving even the territorial gains. The key problem remained, however, to forecast the so-called ‘zero hour’ when careful timing and the acceptance of risk could guarantee success even at Hitler’s doorstep.